2012
DOI: 10.1016/j.neuroscience.2012.09.066
|View full text |Cite
|
Sign up to set email alerts
|

Combination treatment of stroke with sub-therapeutic doses of Simvastatin and human umbilical cord blood cells enhances vascular remodeling and improves functional outcome

Abstract: Human umbilical cord blood cells (HUCBCs) have been employed as a restorative treatment for experimental stroke. In this study, we investigated whether transplantation of sub-therapeutic doses of HUCBCs and Simvastatin enhances cerebral vascular remodeling after stroke. Adult male Wistar rats (n=34) were subjected to transient middle cerebral artery occlusion (MCAo) and treated with: phosphate buffered solution (PBS, gavaged daily for 7 days); Simvastatin (0.5mg/kg, gavaged daily for 7 days); HUCBCs (1x106, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 56 publications
0
16
1
Order By: Relevance
“…The results of this study are in clear contrast with previously reported findings from our 3 and other groups 6,28 that indicated a noticeable benefit of experimental HUCB MNC transplantation after stroke. However, next to a considerable body of indications corroborating the therapeutic efficacy of HUCB MNC after stroke, some investigators were unable to reproduce therapeutic findings, especially when applying more demanding functional tests as in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of this study are in clear contrast with previously reported findings from our 3 and other groups 6,28 that indicated a noticeable benefit of experimental HUCB MNC transplantation after stroke. However, next to a considerable body of indications corroborating the therapeutic efficacy of HUCB MNC after stroke, some investigators were unable to reproduce therapeutic findings, especially when applying more demanding functional tests as in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, direct release of human neurotrophins by cord blood cells as shown in in vitro experiments 27 cannot be ruled out by our study design and might account for discrepancies with the literature. 10,28 But even if present, it would not have had an effect on the primary and secondary endpoints assessed. Moreover, we performed analysis of growth factor mRNA expression only up to 2 days after stroke, as previous studies suggested that gene expression functionally related to processes of brain plasticity is initiated very quickly after stroke.…”
Section: Discussionmentioning
confidence: 94%
“…UCB cells have produced functional recovery and vascular remodeling after stroke. 56 UCB has shown promise and is in clinical trials for the treatment of patients with chronic spinal cord injury. 57 The IV infusions of human UCB ameliorated the consequences of prenatal hypoxic injury in a baby rabbit model of hypoxic ischemic encephalopathy.…”
Section: Regenerative Medicinementioning
confidence: 99%
“…[9][10][11] In this context, prompt revascularization of stroke is associated with improved outcome. [12][13][14] For instance in humans, elevated levels of vascular endothelial growth factor (VEGF) are observed after stroke, and increased microvascular density correlates with a better outcome. 15,16 In animal models, intracerebral injections of proangiogenic factors greatly enhance motor functions.…”
mentioning
confidence: 99%